2005
DOI: 10.1038/sj.onc.1209232
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine activation of PDGFRα promotes the progression of ovarian cancer

Abstract: Platelet-derived growth factor receptor (PDGFR)a expression was found in ovarian cancer cells and tumors by microarray hybridization. This led us to test whether ovarian cancers also produce ligands for this receptor, as this would demonstrate that such malignancies support their own growth and spread through autocrine activation. We assayed the expression of ligands for the PDGFR in ovarian tumors, cell lines and peritoneal fluid using RT-PCR, immunohistochemistry (IHC) and ELISA. We detected strong mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
95
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 35 publications
8
95
0
Order By: Relevance
“…Experiments in vivo have shown that PDGFRs activated by PDGFs modulate Akt and MAPK phosphorylation and significantly influence ovarian cancer cell proliferation and tumor expansion. 16 These observations suggest that the PDGF-PDGFR system may play a functional role in the progression of ovarian cancers through autocrine or paracrine activation within the tumor tissues.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Experiments in vivo have shown that PDGFRs activated by PDGFs modulate Akt and MAPK phosphorylation and significantly influence ovarian cancer cell proliferation and tumor expansion. 16 These observations suggest that the PDGF-PDGFR system may play a functional role in the progression of ovarian cancers through autocrine or paracrine activation within the tumor tissues.…”
mentioning
confidence: 89%
“…Although such mutations and gene amplification have not been described previously in ovarian cancers, recent studies have demonstrated that PDGFR-a, PDGFR-b, and PDGF-AB are commonly expressed in ovarian cancers at frequencies as high as 87, 81, and 67%, respectively. [13][14][15][16] Moreover, Henriksen et al 17 have reported that PDGFRs or PDGFs were not detected in any of the benign ovarian tumors or normal ovarian epithelium they examined. Experiments in vivo have shown that PDGFRs activated by PDGFs modulate Akt and MAPK phosphorylation and significantly influence ovarian cancer cell proliferation and tumor expansion.…”
mentioning
confidence: 96%
“…2). [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Several types of cancers, particularly those derived from the ovary, prostate, breast, lung, brain, skin, and bone, express PDGFRa on the malignant cells themselves (Table 1). 22 In 1 experiment in which a human tumor array was probed with a cross-reactive polyclonal rabbit antibody to PDGFRa, PDGFRa expression was noted in approximately 95% of osteosarcomas and chondrosarcomas, in 77% of prostate cancers, in 52% of ovarian cancers, in 65% of breast cancers, and in 51% of lung cancers (N. Loizos, ImClone Systems, unpublished results).…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
“…A separate investigation demonstrated strong immunohistochemical staining (2 to 3þ) in 89% of the clear cell histologic subtype of ovarian cancers. 50 Gene amplifications of PDGFRa have been identified in a subset of malignant gliomas, 62 and activating mutations of PDGFRa have been discovered in a proportion of gastrointestinal stromal tumors. 63 Tumor PDGFRa expression has been associated with disease progression in renal cell cancer, 64 diminished survival in ovarian cancer, 56 lymph node metastasis in breast cancer, 58 and bone metastases in prostate cancer.…”
Section: The Pdgf/pdgfr Axis In Cellular Signalingmentioning
confidence: 99%
See 1 more Smart Citation